Urgensi Autentikasi dan Legalisasi Arsip Pertanahan Hasil Digitalisasi - Farista Dewi Anindyati; Abdul Haris Farid; Dwi Wulan Titik Andari (Sekolah Tinggi Pertanahan Nasional, 2020)
Land archive is the living archive of that must be fully maintained. As things goes, Sleman Land Office does digitalization archives to Gambar Ukur, Surat Ukur, Buku Tanah and Warkah by using a web-based application system which is called the Laris application. The research is aimed at finding out the reason why the office is doing digitalization with Laris application and finding out wheter this digitalized archive has been able to replace the original file in the form of paper. This research was conducted with a qualitative method with a descriptive approach Based on research results, obtained information that the digitalization of land records carried out in the Sleman’s Land office which has been done since year 2014 not solely done to change the format of analog files to digital files, but is expected to able provide more comprehensive benefits related to the acceleration of land services so that in practice it uses the Laris application. However, the existence of this digitalized archive still not able to replace the position of analog archive in manner so that the analog archive is still maintained. Therefore, its important to authentication and legalization so the archive of digitalization result legally strong.